2020
DOI: 10.1159/000509296
|View full text |Cite
|
Sign up to set email alerts
|

Topical Over-the-Counter Antiaging Agents: An Update and Systematic Review

Abstract: Over-the-counter antiaging formulations aim to prevent or minimize the signs of aging skin, and to maintain the benefits obtained from different cosmetic procedures. Even though a huge selection of such products is available on the market, evidence and good clinical practice of the data supporting their use are oftentimes lacking. In this systematic review, the authors reviewed scientific data available in the published literature on the most common ingredients used in antiaging cosmetics, with a particular fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…Considering the limitations of the clinical studies performed, the use of retinoid cosmetics as a tretinoin equivalent is not justified and evidence-based. Our findings are consistent with previous studies that also suggested that in the case of cosmeceuticals, the positive study outcome cannot be considered relevant information for clinical decision-making because most of the performed studies have significant methodological issues and deficiencies in study design that limit the relevance of the results [81,168].…”
Section: Clinical Evidence For Conventional Formulationssupporting
confidence: 91%
See 1 more Smart Citation
“…Considering the limitations of the clinical studies performed, the use of retinoid cosmetics as a tretinoin equivalent is not justified and evidence-based. Our findings are consistent with previous studies that also suggested that in the case of cosmeceuticals, the positive study outcome cannot be considered relevant information for clinical decision-making because most of the performed studies have significant methodological issues and deficiencies in study design that limit the relevance of the results [81,168].…”
Section: Clinical Evidence For Conventional Formulationssupporting
confidence: 91%
“…Also, there is a lack of clinical evidence for the antiaging efficacy of the other retinyl esters since most of the performed studies have limitations, such as a small number of participants and/or a lack of a vehicle control group. In general, placebo-controlled double-blind studies as a standard in clinical research are lacking for cosmetics [ 168 ]. Considering the limitations of the clinical studies performed, the use of retinoid cosmetics as a tretinoin equivalent is not justified and evidence-based.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-aging therapies have seen an increase in focus from the medical research community over the last few decades [ 43 ]. While surgical techniques for rejuvenation have been heavily described, both plastic surgery and dermatology have strived to develop non-invasive options for treatment and prevention of facial aging [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anti-aging therapies have seen an increase in focus from the medical research community over the last few decades [ 43 ]. While surgical techniques for rejuvenation have been heavily described, both plastic surgery and dermatology have strived to develop non-invasive options for treatment and prevention of facial aging [ 43 , 44 ]. The study by Berardesca et al showed a significantly greater increase in gross elasticity and net elasticity versus vehicle alone at weeks 4 and 8 as well as improvements in parameters associated with wrinkling (volume), smoothness, and uniformity [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of cosmeceuticals with natural or synthetic active ingredients are available in the market to treat photoaging, however, evidence based data is lacking for most. Randomized placebo controlled studies with positive outcome are available for retinoids, α‐hydroxy acids such as glycolic, and some peptide etc 1 . Retinoids have strongest evidence showing clinical and histologic improvement in photoaged skin, however irritant dermatitis with retinoid therapy has limited their acceptance by patients 2 .…”
Section: Introductionmentioning
confidence: 99%